Renal cell carcinoma with cutaneous metastasis in a dog - Carvalho, Pablo H.; Conceição, Lissandro G.; Barros, Márcia S.; Moreira, José C. L. Moreira; Amorim, Renée Laufer [UNESP]; Pinczowski, Pedro [UNESP] (My University, 2011)
The present report describes the occurrence of skin metastasis in a dog with primary renal carcinoma. The clinical findings included progressive weight loss, inappetence, palpable abdominal mass and cutaneous nodules. The histopathological examination was carried out after unilateral nephrectomy and was confirmed by immunohistochemistry. The immunohistochemical and histopathological findings characterized this case as renal cell carcinoma with skin metastasis.
Keywords: Diseases of dogs; Immunohistochemistry; Renal carcinoma; Renal tumors; Skin metastasis; Canis familiaris